An Account of Global Intraindustry Trade, 1962-2006 - Brülhart, Marius (Washington, DC: World Bank, 2012)
A comprehensive description of intra-industry trade patterns and trends, using data on more than 39 million bilateral trade flows is given. In 2006, 27 percent of global trade was intraindustry, if measured at the finest (5-digit) level of statistical aggregation, and 44 percent if measured at a coarser (3-digit) level of statistical aggregation. The observed steady growth in global intra-industry trade since the early 1960s suggests a process of world-wide structural convergence: economies are becoming more similar over time in terms of their sectoral compositions. In particular since the 1990s, this trend appears to be driven to a significant extent by the international fragmentation of vertical production chains. Intra-industry trade is a high-income and middle-income country phenomenon: African trade remains overwhelmingly of the inter-industry type. Moreover, the observed increase in intra-industry trade was not accompanied by a comparable increase in marginal intra-industry trade, suggesting that trade-induced adjustment pressures remain potentially important.